Serum creatinine to absolute lymphocyte count ratio effectively risk stratifies patients who require intensive care in hospitalized patients with coronavirus disease 2019. Issue 38 (23rd September 2022) - Ngiam, Jinghao Nicholas; Liong, Tze Sian; Chew, Nicholas W.S.; Li, Tony Yi-Wei; Chang, Zi Yun; Lim, Zhen Yu; Chua, Horny Ruey; Tham, Sai Meng; Tambyah, Paul Anantharajah; Santosa, Amelia; Cross, Gail Brenda; Sia, Ching-Hui
Abstract : Patients with preexisting kidney disease or acute kidney injury had poorer outcomes in coronavirus disease 2019 (COVID-19) illness. Lymphopenia was associated with more severe illness. Risk stratification with simple laboratory tests may help appropriate site patients in a cost-effective manner and ease the burden on healthcare systems. We examined a ratio of serum creatinine level to absolute lymphocyte count at presentation (creatinine-lymphocyte ratio, CLR) in predicting outcomes in hospitalized patients with COVID-19. We analyzed 553 consecutive polymerase chain reaction-positive SARS-COV-2 hospitalized patients. Patients with end-stage kidney disease were excluded. Serum creatinine and full blood count (FBC) examination were obtained within the first day of admission. We examined the utility of CLR in predicting adverse clinical outcomes (requiring intensive care, mechanical ventilation, acute kidney injury requiring renal replacement therapy or death). An optimized cutoff of CLR > 77 was derived for predicting adverse outcomes (72.2% sensitivity, and 83.9% specificity). Ninety-seven patients (17.5%) fell within this cut off. These patients were older and more likely to have chronic medical conditions. A higher proportion of these patients had adverse outcomes (13.4% vs 1.1%, P < .001). On receiver operating curve analyses, CLR predicted patients who had adverse outcomes well (area under curve [AUC] = 0.82, 95%CI 0.72–0.92), which was comparable to other laboratory tests like serum ferritin, C-reactive protein and lactate dehydrogenase. Elevated CLR on admission, which may be determined by relatively simple laboratory tests, was able to reasonably discriminate patients who had experienced adverse outcomes during their hospital stay. This may be a simple and cost-effective means of risk stratification and triage.